Sensorimotor Behaviour Reflects Lexical and Grammatical Aspect in Czech: An Eye Tracking Study - Kořenář, Michal (Poljarnyj vestnik, 2016)
Thinking and speaking about events is a process tightly connected with time perception. We can express when an event has occurred with respect to other events, whether it was a durative or a one-time event, whether it was an ongoing or already finished event, etc. Every human language has its own way and extent to which this complex temporal structure of experienced events is expressed. Upon hearing a story we construct a mental representation of the communicated event (e.g. Givón 1992). Some studies show that this construction already evolves during online processing, thanks to instantly accessible language processing cues (Altman and Kamide 1999, Ferretti, McRae and Hatherell 2001, McRae, Ferretti and Amyote 1997). These cues are employed to capture the intricate temporal structure of the story, for instance. They arise from the interplay of the three basic linguistic components (structure, meaning and function) and as such are consistent with a constructional view of language (e.g. Fillmore 1988). Even subtle changes of any of the linguistic cues may lead to a different mental representation. Examples of the sources of grammatical markers and lexical categories from which the linguistic cues arise are grammatical and lexical aspect. In the linguistic field, a lot of attention has been paid to analyses of how those sources of temporal cues function within a language system. However, there is a lack of empirical data on how grammatical and lexical aspect interact, and what the effects of such an interaction are. The present study aims to investigate the link between the complex system of temporal cues and sensorimotor representation in Czech speakers, with specific focus on grammatical verb aspect and so-called event telicity, i.e. lexical aspect, all of which will be further described below.